2018
DOI: 10.1093/ofid/ofx279
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Primary Care Physicians Associated With High Outpatient Antibiotic Prescribing Volume

Abstract: Our objective was to identify characteristics associated with high-volume antibiotic prescribing among office-based primary care physicians to target antibiotic stewardship efforts. Physicians aged 40 years and older who were male, located in the South, and in solo or 2-physician practices prescribed higher volumes of antibiotics than their peers by specialty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 8 publications
4
24
0
1
Order By: Relevance
“…Although the literature continues to demonstrate ongoing issues with unnecessary antibiotic exposure for ARIs and risk factors for inappropriate prescribing in the outpatient setting, [17][18][19][20][21][22] a paucity of data exists on the impact of residents on antibiotic use in primary care. Gaur et al 25 reported that during outpatient visits for a diagnosis suggestive of a viral URI in children, antibiotic prescribing occurred more commonly among attending staff physicians than trainees (36.5% vs 19.5%; OR, 0.44; 95% CI, 0.33-0.59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the literature continues to demonstrate ongoing issues with unnecessary antibiotic exposure for ARIs and risk factors for inappropriate prescribing in the outpatient setting, [17][18][19][20][21][22] a paucity of data exists on the impact of residents on antibiotic use in primary care. Gaur et al 25 reported that during outpatient visits for a diagnosis suggestive of a viral URI in children, antibiotic prescribing occurred more commonly among attending staff physicians than trainees (36.5% vs 19.5%; OR, 0.44; 95% CI, 0.33-0.59).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have attempted to determine risk factors for unnecessary antibiotic prescribing in the outpatient setting [17][18][19][20][21][22] ; however, a paucity of data exists for antibiotic prescribing practices at residency-based primary care settings, which have unique forces impacting the practice of evidenced-based medicine. Before implementing ASP initiatives to optimize ARI-associated antibiotic use within the Allegheny Health Network (AHN), we aimed to identify characteristics associated with inappropriate antibiotic prescribing for ARIs among physicians in internal medicine (IM) residencyebased primary care offices.…”
mentioning
confidence: 99%
“…Our study's findings are consistent with previous studies' antibiotic prescribing rates for acute upper respiratory infections, in that rates still remain high over recent years. [18][19][20] The correlation between provider characteristics and increased antibiotic use is explained by a range of factors, such as the importance placed on patient satisfaction surveys, years of practice, time pressures, and longstanding relationships between the provider and patient. 2,[20][21][22][23][24][25] In our study, physician specialists and providers 35 years of age were significantly less likely to prescribe antibiotics in AAB, likely explained by the notion that physician specialists are not typically first-line providers who treat uncomplicated AAB.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been more endorsements from medical organizations and societies that highlight the importance of appropriate antibiotic use in the outpatient setting. 20,26 The patient-level characteristics identified in this study serve as a general description of the patient population at Baylor Scott & White Health who required medical care for a common viral diagnosis. This can be a useful baseline when evaluating trends and patterns from a patient-level perspective over time.…”
Section: Discussionmentioning
confidence: 99%
“…IQVIA data are the most complete source of outpatient population-based antibiotic data in many jurisdictions. 4,12,21,40 However, this database has not been externally validated and it is possible that the estimates of antibiotic use were less precise in certain regions with poorer coverage. Pharmacy dispensing data may not accurately represent antibiotic consumption as patient adherence can vary.…”
Section: Limitationsmentioning
confidence: 99%